Small bowel stromal tumour revealed by a lower gastrointestinal bleeding - Kassi, Assamoi B. F.; Lebeau, R.; Kacou, Y. S.; N’dah, K. J. (International Journal of Research in Medical Sciences, 2016)
Small bowel stromal tumour must be systematically researched in the presence of obscure and persistent low gastrointestinal bleeding despite a normal endoscopic examination (OGDF and colonoscopy). Video capsule endoscopy is the best diagnosis examination; if it is not available a CT enterography could be useful. Surgical treatment is effective on localized and weak malignancy small bowel stromal tumours.